Mitochondrial coupling and capacity of oxidative phosphorylation in skeletal muscle of Inuit and Caucasians in the arctic winter - Gnaiger, E.; Boushel, R.; Søndergaard, H.; Munch-Andersen, T.; Damsgaard, R.; Hagen, C.; Díez-Sánchez, C.; Ara, I.; Wright-Paradis, C.; Schrauwen, P.; Hesselink, M.; Calbet, J. A. L.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2015)
During evolution, mitochondrial DNA haplogroups of arctic populations may have been selected for lower coupling of mitochondrial respiration to ATP production in favor of higher heat production. We show that mitochondrial coupling in skeletal muscle of traditional and westernized Inuit habituating northern Greenland is identical to Danes of western Europe haplogroups. Biochemical coupling efficiency was preserved across variations in diet, muscle fiber type, and uncoupling protein‐3 content. Mitochondrial phenotype displayed plasticity in relation to lifestyle and environment. Untrained Inuit and Danes had identical capacities to oxidize fat substrate in arm muscle, which increased in Danes during the 42 days of acclimation to exercise, approaching the higher level of the Inuit hunters. A common pattern emerges of mitochondrial acclimatization and evolutionary adaptation in humans at high latitude and high altitude where economy of locomotion may be optimized by preservation of biochemical coupling efficiency at modest mitochondrial density, when submaximum performance is uncoupled from VO2max and maximum capacities of oxidative phosphorylation.